Molecular targets in cancer therapy: the Ron approach - Serena Germano; Giovanni Gaudino (Frontiers Media S.A., 2011)
The receptor tyrosine kinase Ron and its ligand, Macrophage Stimulating Protein (MSP), mediate multiple processes involved in the control of cell proliferation, migration and protection from apoptosis. Dysregulated signaling of Ron, due to hyperactivation or loss of negative regulation, is involved in tumor progression and metastasis. Growing evidence indicates that Ron is abnormally expressed and activated in certain types of primary epithelial cancers (i.e. breast, colon, lung, pancreas, bladder and thyroid), where it critically contributes to the maintenance of tumorigenic and invasive phenotype. Furthermore, a positive association between aberrant Ron expression and aggressive biological indicators as well as a worse clinical outcome have been reported in breast, bladder and thyroid carcinomas. Different approaches have proved effective in targeting receptor activation/expression both in vitro and in animal models, leading to reversion of the tumorigenic phenotype. Altogether these results show that Ron is an attractive molecular target for clinical intervention.